Acehnese Ethnoscience as an Interdisciplinary Approach in Physics Education: Innovating in the Era of Merdeka Belajar - Saminan, Saminan; Irwandi, Irwandi; Kamza, Muhjam; bin Rasul, Mohammad Sattar (SCAD Independent, 2024)
Various efforts have been made to improve students’ understanding of basic physics concepts, but their mindset in constructing knowledge remains problematic. The learning process has yet to engage long-term memory, preventing meaningful analysis-level understanding. This research aimed to activate students’ thinking patterns based on ethnoscience through learning tools such as modules, semester learning plans (RPS), and student worksheets (LKM) that are valid, practical, and efficient. The research used the R&D method with the ADDIE approach, involving 2 expert validators and all Physics Education students at FKIP USK enrolled in basic physics courses in 2022. The results indicated that the ethnoscience-based basic physics learning tools of the Acehnese community, which include modules, RPS, and LKM, effectively supported Merdeka Belajar and have been validated for their validity, practicality, and efficiency. Students were highly motivated and impressed by the concept of measurement in physics, which has long been practiced by the Acehnese community, such as in paying zakat fitrah during Ramadan. The scientifically understood volume-measuring tools used by students were not significantly different from the ethnoscience tools used by the Acehnese community. Ethnoscience facilitates meaningful learning by analyzing context, content, and literacy.